2020
DOI: 10.1016/j.foodchem.2020.126377
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ligusticum chuanxiong polylactic acid microspheres: A promising way to enhance the hepatoprotective effect on bioactive ingredients

Abstract: Fabrication of Ligusticum chuanxiong polylactic acid microspheres: A promising way to enhance the hepatoprotective effect on bioactive ingredients, Food Chemistry (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As an important dual-use resource of medicine and food, CX is more popular in the demand of natural products to promote people's health. 10 In the past, researchers often focused on the rhizomes of CX, ignoring the potential value of its other parts. This practice not only causes a serious waste of resources, but also is not conducive to the comprehensive development and utilization of CX resources.…”
Section: Introductionmentioning
confidence: 99%
“…As an important dual-use resource of medicine and food, CX is more popular in the demand of natural products to promote people's health. 10 In the past, researchers often focused on the rhizomes of CX, ignoring the potential value of its other parts. This practice not only causes a serious waste of resources, but also is not conducive to the comprehensive development and utilization of CX resources.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ligustrazine on pre-clinical studies are far from satisfactory. Recent study indicated that ligustrazinepolylactic acid (PLA) sustained-release microspheres might be a promising agent due to the characteristics of stable and sustained release effects on bioactive ingredients [21] . As PLA is emerging as an ideal drug carrier for its favorable biocompatibility and biodegradable [22] .…”
Section: Introductionmentioning
confidence: 99%
“…A pyrazine and its several derivants, such as tetramethylpyrazine, have been detected in Maotai, Laobaigan, Yanghe River Daqu, and Fenjiu. Tetramethylpyrazine is the main active ingredient of Rhizoma Ligustici Chuanxiong, a Chinese herbal that has long been used to treat liver disease and protect the liver from fibrosis (115,116). It has antioxidation properties and enhances triglyceride degradation.…”
Section: The Effects and Putative Mechanisms Of The Main Flavor Compo...mentioning
confidence: 99%